Participatory Management of Irrigation System in North Eastern Region of India. (April 2018) - Devi, Chandam Victoria
The demand of water by various competing sectors, such as industry, power, drinking and irrigation, is increasing while the supply of available fresh water remains the same. This calls for efficient use of water in all sectors especially irrigation, which consumes the highest amount of water in India. Due to recurrence of drought and flood India suffered from famine, so after the Independence the government has rigorously pursued the construction of irrigation dams to increase agricultural production and meet the increasing demand of food. Construction of dams was given priority than management of irrigation projects. But due to a large gap between irrigation potential created and irrigation potential utilized, there was a paradigm shift in the irrigation sector. As a result, the concept of participatory irrigation management (PIM) was widely spread through seminars, National Water Policies and specific irrigation Command Area Development (CAD) programme. The first National Water Policy in 1987 and the subsequent policies had provisions for involvement of farmers in irrigation management for efficient use of irrigation water. Many states in India implemented PIM Act under the policy. It also applies to the northeastern region (NE region) of India. This region has a traditional irrigation system such as bamboo drip irrigation in Meghalaya, water conservation among the Apatanis of Arunachal Pradesh, zabo system of Nagaland and dong irrigation among the Bodos of Assam which are traditionally managed by the farmers. This article examines the farmers' participation in irrigation management in the NE region. It attempts to highlight the changes of PIM policies, involvement of farmers or the Water Users' Associations (WUAs) in irrigation management, constraints and suggest ways to strengthen them for efficient use of irrigation water in the NE region of India.